2022
DOI: 10.1038/s41467-022-34809-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation disrupts long-distance electron transport in cytochrome c

Abstract: It has been recently shown that electron transfer between mitochondrial cytochrome c and the cytochrome c1 subunit of the cytochrome bc1 can proceed at long-distance through the aqueous solution. Cytochrome c is thought to adjust its activity by changing the affinity for its partners via Tyr48 phosphorylation, but it is unknown how it impacts the nanoscopic environment, interaction forces, and long-range electron transfer. Here, we constrain the orientation and separation between cytochrome c1 and cytochrome c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…Longer charge exchange distances are described by thermally activated multistep mechanisms; however they are incompatible with the available data of temperature-independent ETp. , It has been suggested that electrostatic potential driving ET induces a partial delocalization of the bridge electronic states able to promote long-range electron transfer without thermal activation . For the pair hC c /pC c 1 , molecular dynamics calculations revealed a cation depletion region between the interacting partners that hinders charge screening, extending the electric field between redox partners across the electrolyte interface. , In other words, the cognate partners establish a Gouy–Chapman conduit between them. , The results presented here support this view, as long-distance charge transport (low β) observed for Pc apo interacting with PSI is absent when Pc apo faces a noncognate sequence like that of the pIQAcys peptide. This extended charge exchange range of Pc apo /PSI with respect to Pc holo /PSI is favored for positive bias, driving electrons from Pc to PSI, as it occurs in nature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Longer charge exchange distances are described by thermally activated multistep mechanisms; however they are incompatible with the available data of temperature-independent ETp. , It has been suggested that electrostatic potential driving ET induces a partial delocalization of the bridge electronic states able to promote long-range electron transfer without thermal activation . For the pair hC c /pC c 1 , molecular dynamics calculations revealed a cation depletion region between the interacting partners that hinders charge screening, extending the electric field between redox partners across the electrolyte interface. , In other words, the cognate partners establish a Gouy–Chapman conduit between them. , The results presented here support this view, as long-distance charge transport (low β) observed for Pc apo interacting with PSI is absent when Pc apo faces a noncognate sequence like that of the pIQAcys peptide. This extended charge exchange range of Pc apo /PSI with respect to Pc holo /PSI is favored for positive bias, driving electrons from Pc to PSI, as it occurs in nature.…”
Section: Discussionmentioning
confidence: 99%
“…To answer them, it seems reasonable to involve the aqueous solution region confined between the proteins and to avoid explanations based on conventional quantum tunneling since reported charge exchange distances ,,, exceed the range accessible by one- and two-step electron tunneling. Longer charge exchange distances are described by thermally activated multistep mechanisms; however they are incompatible with the available data of temperature-independent ETp. , It has been suggested that electrostatic potential driving ET induces a partial delocalization of the bridge electronic states able to promote long-range electron transfer without thermal activation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyto c activities are tightly regulated by posttranslational modifications [ 149 ]. Specifically, phosphorylation can serve as the switch between the multiple activities of the protein [ 150 ].…”
Section: Cytochrome C Apoptotic and Non-apoptotic Functionsmentioning
confidence: 99%